Anti-inflammatory effect of curcuminoids and their analogs in hyperosmotic human corneal limbus epithelial cells - Ngamjit Kasetsuwan; Usanee Reinprayoon; Lita Uthaithammarat; Amornpun Sereemaspun; Nutchanart Sae-liang; Waraluck Chaichompoo; Apichart Suksamrarn (BMC, 2024)
Abstract Background To assess the efficacy of curcuminoids (curcumin, demethoxycurcumin, bisdemethoxycurcumin [BDC]) and their analogs (tetrahydrocurcumin [THC], tetrahydrodemethoxycurcumin [THDC], tetrahydrobisdemethoxycurcumin) in reducing inflammatory cytokines and their toxicity to primary human corneal limbal epithelial cells, these cells were cultured and exposed to these compounds. Methods The PrestoBlue assay assessed cell viability after treatment. Anti-inflammatory effects on hyperosmotic cells were determined using real-time polymerase chain reaction and significance was gauged using one-way analysis of variance and Tukey's tests, considering p-values < 0.05 as significant. Results Curcuminoids and their analogs, at 1, 10, and 100 µM, exhibited no effect on cell viability compared to controls. However, cyclosporin A 1:500 significantly reduced cell viability more than most curcuminoid treatments, except 100 µM curcumin and BDC. All tested curcuminoids and analogs at these concentrations significantly decreased mRNA expression levels of tumor necrosis factor-α, interleukin (IL)-1β, IL-6, IL-17 A, matrix metallopeptidase-9, and intercellular adhesion molecule-1 after 90 mM NaCl stimulation compared to untreated cells. Furthermore, proinflammatory cytokine levels from hyperosmotic cells treated with 1, 10, and 100 µM curcumin, 100 µM BDC, 100 µM THC, 1 and 100 µM THDC mirrored those treated with cyclosporin A 1:500. Conclusion The anti-inflammatory efficiency of 1 and 10 µM curcumin, 100 µM THC, 1 and 100 µM THDC was comparable to that of cyclosporin A 1:500 while maintaining cell viability.